Analytical investigation of rectangular steel pipe shear connector. (February 2021) - Zhu, X.; Takimoto, K.; Tanaka, H.
Abstract: Rectangular steel pipe (RSP) which is a new kind of connector in a composite slab of steel–concrete has been proposed. Research on the shear properties of RSPs is limited, but such data are needed if RSPs are to be used as shear connectors in composite slabs. Here, a nonlinear finite-element (FE) model that accounts for the nonlinear material properties and the RSP–concrete interface is proposed. A comparison between the finite element method (FEM) results and the static push-out test data showed good agreement in terms of shear stiffness, shear capacity, and failure mode. This verified FE model was then used in a parametric study to investigate the effects of constraint in push-out test, concrete stiffness, concrete compressive strength, RSP dimensions, RSP thickness, and RSP welding length on RSP shear capacity. The analytical results showed that constraint, concrete strength, RSP dimensions, RSP thickness, and welding length all affected RSP shear capacity, whereas concrete stiffness showed light effects. The shear capacity obtained using the FE model was compared with the calculated result using the Japan Society of Civil Engineers (JSCE) equations for the shear capacity of L-shaped channels.